Impact of delaying botulinum toxin treatment in patients with migraine during the COVID-19 pandemic - Henrique Nascimento; Gonçalo Videira; Sara Duarte; Carlos Correia; Carlos Andrade (Arquivos de Neuro-Psiquiatria)
Background Due to coronavirus disease 2019 (COVID-19) pandemic response measures, the administration of botulinum toxin (BTX) was delayed for many patients during the first lockdown period in Portugal.